DESCRIPTION OF THE IMPLEMENTATION OF SUPERVISION OF LECTURER PERFORMANCE AND IMPROVEMENT IN THE LLDIKTI IV REGION OF WEST JAVA (CASE STUDY: BUDI LUHUR HEALTH COLLEGE, CIMAHI CITY) - Damai Yanti; Lilis Sakuroh; Elis Ela Susila; Dadang (Adisam Publisher, 2026)
This study aims to describe the implementation of academic supervision at STIKes Budi Luhur Cimahi and analyze its influence on improving lecturers' performance and competence. Academic supervision is an important part in supporting the implementation of the Tridharma of Higher Education, especially in the fields of teaching, research, and community service. This study uses a qualitative descriptive approach with data collection techniques through in-depth interviews, direct observation, and analysis of academic documents. The results of the study indicate that academic supervision at STIKes Budi Luhur Cimahi is carried out in a structured manner through the Quality Assurance Unit (UPM) with a focus on class observation, student surveys, and evaluation of learning documents. Supervision has a positive impact on improving lecturers' competence, especially in designing practice-based learning strategies that are relevant to the needs of the world of work in the health sector. However, the implementation of supervision still faces obstacles such as limited supporting facilities, lack of training for supervisors, and lecturers' resistance to the supervision process. This study concludes that effective academic supervision is not only an evaluation tool, but also an instrument to support the continuous professional development of lecturers. Strategic recommendations include improving learning facilities, routine training for lecturers and supervisors, and a more collaborative supervision approach. With these steps, STIKes Budi Luhur Cimahi can continue to improve the quality of education and produce competent graduates in the health sector.